INTERACTIVE MEDIA AND ITS EFFECT TOWARD THE IMPROVEMENT OF SOCIAL SCIENCES LEARNING OUTCOMES IN ELEMENTARY SCHOOL LEVEL - Dine Trio Ratnasari (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
Learning Social Sciences is identical to lecturing and monologue by teachers to students. It is caused by the students’ low interest in learning and then, the students’ learning outcomes in Social Sciences are poor. The present study examines the effect of interactive media on students’ learning outcomes of elementary school in Social Sciences subject. A Classroom Action Research was applied. The researcher implemented interactive media to Social Sciences subject by the aim of improving the process of learning and the learning outcomes. This research was conducted at SDN Kaduagung Timur 1, involving 26 students of 4th grade. The results showed that the implementation of interactive media in the form of CDs could improve the learning outcomes and activities of teachers and students in Social Sciences subject at SDN Kaduagung Timur 1. This can be seen from the average score of students’ learning outcomes and the activities of the teachers and the students in the first cycle which have increased, that is from 63.26 to 73.84 and the student learning activities also increased from 62.5% to 100%. This number affected the mastery of student learning outcomes in cycle 1 to reach 63.26 while in cycle 2 it increased to 73.84. From them, it indicates that the mastery of student learning outcomes has increased from cycle I to cycle II by 10.58%. Hence, the implementation of interactive media is able to improve learning outcomes and activities of teachers and students in Social Sciences subject.